Brassica oleracea var italica and Their By-Products as Source of Bioactive Compounds and Food Applications in Bakery Products - Jhazmin Quizhpe; Pablo Ayuso; María de los Ángeles Rosell; Rocío Peñalver; Gema Nieto (Foods)
Broccoli (Brassica oleracea var. italica) is one of the most consumed cruciferous crops in the world, with China and Spain acting as the main producers from outside and within the EU, respectively. Broccoli florets are edible, while the leaves and stalks, discarded in the field and during processing, are by-products. Therefore, the objective of this study was to conduct a comprehensive review of the nutrient and phytochemical composition of broccoli and its by-products, as well as its beneficial effects. In addition, the study highlights the revalorization of broccoli by-products through innovative green technologies and explores their potential use in bakery products for the development of functional foods. The studies suggested that broccoli is characterized by a high content of nutrients and bioactive compounds, including vitamins, fiber, glucosinolates, and phenolic compounds, and their content varied with various parts. This high content of value-added compounds gives broccoli and its various parts beneficial properties, including anti-cancer, anti-inflammatory, antioxidant, antimicrobial, metabolic disorder regulatory, and neuroprotective effects. Furthermore, broccoli and its by-products can play a key role in food applications by improving the nutritional profile of products due to their rich content of bioactive compounds. As a result, it is essential to harness the potential of the broccoli and its by-products that are generated during its processing through an appropriate agro-industrial revalorization, using environmentally friendly techniques.